Angelina Ballerina - Katharine holabird (Pleasent Company publications, 2000)
Angelina Ballerina is the picture book that first introduced Angelina to her adoring fans. This tiny dancer has proved to have enormous staying power--she has been a hugely popular character for more than twenty years. And Angelina's popularity only continues to grow. She is even the spokescharacter for National Dance Week.With Katharine Holabird's lively writing and Helen Craig's charming illustrations, the original story about the feisty little mouse who wants nothing more than to dance still keeps young ballerinas leaping with delight.
Keywords: Read Aloud -- Read Aloud